Genome-wide analysis of the harbour porpoise (Phocoena phocoena) indicates isolation-by-distance across the North Atlantic and potential local adaptation in adjacent waters - Autenrieth, Marijke; Havenstein, Katja; De Cahsan, Binia; Canitz, Julia; Benke, Harald; Roos, Anna; Pampoulie, Christophe; Sigurðsson, Guðjón Már; Siebert, Ursula; Olsen, Morten Tange; Biard, Vincent; Heide-Jørgensen, Mads Peter; et al. (Conservation Genetics, 2024)
The harbour porpoise (Phocoena phocoena), a highly mobile cetacean species of the Northern Hemisphere, inhabits basins that vary broadly in salinity, temperature, and food availability; such variation can drive divergent adaptation among local populations. To shed light on range-wide population structure and local adaptation, we generated ddRAD sequencing data spanning the entire North Atlantic and the Baltic Sea, as well as the Black Sea as an outgroup, and mapped this data to the high-quality draft genome of the species. We identified 11,978 genome-wide SNPs from 150 individuals, which we used for population genetic inferences. Our results support genetic differentiation between North Atlantic and Baltic Sea populations, with Kattegat as a transition zone. Across the North Atlantic the population differentiation is subtle from west to east, congruent with an isolation-by-distance pattern, but indicates a separation of southern North Sea harbour porpoises. We identified genomic outlier regions, i.e., scaffold regions where SNPs with high FST across North Atlantic populations co-occur. Together with the draft genome annotation, these regions could point towards candidate genes for differential local adaptation processes among populations. Furthermore, they enable the development of a SNP panel for routine population assignment which will be useful in a conservation and management context. We identified six outlier loci putatively under positive selection, based on the population structure inferred from the complete SNP set. Our study highlights the value of genome resources in conservation and management and provides a crucial additional resource for the study of harbour porpoise evolution and phylogeny.